Developing A Spatial Audio Motion Cueing (AMC) System for Autonomous Vehicle Users, Navigation and Audio System for Mitigating Motion Sickness - ROSLI, MUHAMMAD LLUQMANUL HAKIM; Ts. Dr. ABD FATHUL HAKIM BIN ZULKIFLI (Progress in Engineering Application and Technology, 2026)
Motion Sickness continue to be a key limitation in the adoption of autonomous vehicle, particulary for passenger who engage in non-driving-related activity. This study present the development and evaluation of a Spatial Audio Motion Cueing (AMC) Systems aimed at reducing motion sickness by delivering directional auditory signals that correspond with vehicle dynamics, allowing passengers to anticipate motion events more effectively. Participants who were classified according to their MSSQ scores and had a moderate susceptibility to motion sickness participated in an experimental on-road study. The participants were split into two groups: a test scenario using AMCS and a baseline scenario without audio cues. Motion Sickness Dose Value, Motion Sickness Assessment Questionnaire, and User Experience Questionnaire instruments were used to measure participants' subjective comfort and sickness levels while they completed a reading task, and physiological reactions were recorded using ECG measurements. The results show that the addition of synchronized spatial audio cues significantly reduced motion sickness symptoms and enhanced comfort levels. The findings imply that AMCS is a successful and non-invasive method for improving passenger satisfaction and assisting with human-centered design in autonomous car systems.